CLOPIDROGEL INDUCED LEUKOCYTOCLASTIC VASCULITIS - Patil, Navin; O, Balaji; Rao, Karthik; A, Talha; Chaitan, Chaitan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Cutaneous adverse drug reactions are very common in a hospital setting while treating patients. Drug-induced vasculitis is a very common form of vasculitis affecting all age groups, and many drugs have been implicated in causing vasculitis. Clopidogrel is an antiplatelet drug used in the management as well as prevention of coronary artery disease. It is known to cause various side effects ranging from bleeding, gastrointestinal disturbances, to skin rashes. Leukocytoclastic vasculitis is a form of hypersensitivity vasculitis and is very rarely seen with clopidogrel. Hence, we report a case of clopidogrel-induced leukocytoclastic vasculitis in an old male patient after coronary stenting.Â 